(untitled) (Scientia Agropecuaria, 2025)
Composting is a key strategy in agroecology that improves soil fertility without causing negative environmental effects. Unlike synthetic fertilizers, compost promotes soil regeneration by increasing its organic matter content, enhancing its structure, and stimulating beneficial microbial activity. This review article examines how composting optimizes the physical, chemical, and biological properties of the soil, increasing its water retention capacity, the availability of essential nutrients such as nitrogen, phosphorus, and potassium, and strengthening crop resilience against diseases and environmental stress. Different composting methods, such as vermicomposting, windrow composting, and Bokashi, are compared, demonstrating that regardless of the method used, compost does not contribute to soil degradation but instead enriches it in a sustainable manner. Additionally, the role of key microorganisms in nutrient mineralization and the improvement of the soil microbiome is highlighted, ensuring a balanced and slow-release supply for plants. Finally, innovative strategies to optimize compost quality using microbial inoculants and natural amendments are discussed, consolidating their role as a sustainable alternative for efficient and environmentally responsible agricultural production.